Hospital readmission with Clostridium difficile infection as a secondary diagnosis is associated with worsened outcomes and greater revenue loss relative to principal diagnosis: A retrospective cohort study. Issue 36 (September 2018) - Zilberberg, Marya D.; Nathanson, Brian H.; Marcella, Stephen; Hawkshead, John Jay; Shorr, Andrew F.
Abstract : Abstract: Recurrent Clostridium difficile infection (rCDI) requiring rehospitalization contributes to poor outcomes, which may differ between patients hospitalized with versus for it. We performed a multicenter retrospective cohort study of rehospitalized adults surviving initial CDI hospitalization. Hospital mortality, length of stay (LOS), 30-day readmission, and mean gap between hospital costs and Diagnosis Related Group (DRG) reimbursement served as outcomes. Among the 25.7% (n = 99, 175) survivors requiring rehospitalization, 36, 504 (36.8%) had rCDI (14, 005 [38.4%] principal diagnosis rCDI [PrCDI]). Compared with non-CDI, PrCDI, and secondary diagnosis rCDI [SrCDI] carried lower risk of death (PrCDI odds ratio [OR] 0.52; 95% confidence interval [CI] 0.46, 0.58; SrCDI OR 0.80; 95% CI 0.75, 0.85) and 30-day readmission (PrCDI OR 0.84; 95% CI 0.80, 0.88; SrCDI OR 0.97; 95% CI 0.94, 1.01), and excess LOS (PrCDI 1.8 days; 95% CI 1.7, 2.0; SrCDI 1.4 days; 95% CI 1.3, 1.5), and costs (PrCDI 1399; 95% CI 858, 1939; SrCDI 2809; 95% CI 2307, 3311). Mean gap between hospital costs and DRG reimbursements was highest in SrCDI (13, 803). A rehospitalization within 60-days of an initial CDI hospitalization occurs in approximately 25% of all survivors, 1/3 with rCDI. SrCDI carries worse outcomes than PrCDI. The potential loss of revenue incurred by the hospital is nearly 3-fold higher for SrCDI than PrCDI. Abstract : Supplemental Digital Content is available in the text